Determinants of loyalty on mobile telecommunication network among students of UiTM Samarahan / Sofea Jane Laga - Laga, Sofea Jane (2015)
The purposed of the study to identify the factor of customer loyalty towards mobile telecommunication network and alongside the associations with customer satisfaction and customer loyalty. This research included the factors which is service quality, price perception, convenience, valued offered, trust and satisfaction. The data set by gathered the questionnaire that designed and used random sampling method. A sample 320 was collected from UiTM Samarahan which distributed to campus 1 and campus 2 equally. The finding revealed that there is relationship between satisfaction and customer loyalty. Apart from that, satisfaction is the major factor that can lead to customer loyalty towards mobile telecommunications network.